Preparation and Properties of Microarc Oxidation/Sol - Gel Conductive Coatings on Magnesium Alloy - FU Ming, JIN Meng - hui (Cailiao Baohu, 2021)
An aluminum - doped zinc oxide (ZnO: Al, AZO) transparent conductive film was prepared on the surface of magnesium alloy by micro - arc oxide and sol - gel method. By means of X - ray diffraction (XRD), field emission scanning electron microscopy (FE - SEM), salt spray test, four - probe tester and other analytical testing methods, the effects of the number of coating layers and the annealing temperature on the surface morphology, microstructure, corrosion resistance and conductivity of AZO films were studied. Results showed that the prepared conductive film was composed of crystals with hexagonal wurtzite structure, preferentially oriented in the c - axis; as the number of coating layers and the annealing temperature increased, the sheet resistance of the film was decreased. The prepared AZO films had poor corrosion resistance. Moreover, increasing the number of coating layers did not significantly improve the corrosion resistance of the conductive films. This showed that the AZO thin films prepared in this experiment had poor surface corrosion resistance, and increasing the number of coating layers couldn’t significantly improve the corrosion resistance of conductive film.